The Forgotten Botanist : Sara Plummer Lemmon's Life of Science and Art - Brown, Wynne L. (Book collections on Project MUSE., 2021)
"The Forgotten Botanist tells the story of Sara Lemmon, a little-known and under-appreciated woman of both science and art, who did much of the botanical work attributed to her husband, John Lemmon, and in addition, her gift for drawing in the field, combined with her thirst for scientific knowledge, made her "one of the most accurate painters of nature in the State [of California].""--